Analisis Industri Ritel Di Kota Padang Tanpa Keberadaan Dua Waralaba Ritel Indomaret Dan Alfamart - Awalul Khairi (Journal Of Science Education And Management Business, 2022)
Abstract. The increasing standard of living of people has made many enterpreneurs are interested in opening retail business. Including in Padang city, during the covid-19 pandemic, it did not dampen the desire of entrepreneurs to set up retail businesses in this city. Moreover, there are no large retail franchises that we can find in Padang like other cities in Indonesia.The absence of the large retail franchises in Padang  makes the competitive climate and retail business environment here are different from other big cities in Indonesia. In Padang, local retailers can grow independently by using their own minimarket or supermarket brands.The unique condition of the retail industry in Padang can be analyzed by using the Structure Conduct Performance (SCP) approach. Here the overview of retail competition in Padang will be got. Due to the absence of two large national retailers; PT. Sumber Alfaria Trijaya Tbk (Alfamart) and PT. Indomarco Prismatama (Indomaret), it makes retail competition in Padang occur among the local retailers, the traditional retailers and with the suppliers.  Keywords: Retail, Padang City Retail, Retail environtment, Retail Business Competition, Padang Retail Business